Is More Money Enough to Fix Africa's Transport Infrastructure? - Goldstein, Andrea (OECD Development Centre Policy Insights, 2006)
Transport infrastructure has been dangerously neglected in recent times. Lack of transport infrastructure impedes economic integration and poverty reduction. Involving the private sector in financing the transport infrastructure is proving harder than anticipated